Studi Eksperimental Densitas dan Bilangan Iodin Biodiesel Di Produksi Dari Minyak Goreng Limbah - Sitinjak, Sapriadi; Idris, Muhammad (CV. IRA PUBLISHING, 2024)
This research aims to determine the effect of varying reaction times (60, 70, 80, 90, and 100 minutes) at a temperature of 65℃ and a rotation speed of 1050 rpm on the density and iodine number of biodiesel. The raw material used for biodiesel production is waste cooking oil. This study employs esterification and transesterification processes by reacting catalysts with methanol mixed with waste cooking oil. The catalyst concentration variations used in this study are methanol at a ratio of 1:2 and 0.5% NaOH of the total waste cooking oil. The transesterification product is then settled for approximately 10 minutes. The resulting biodiesel and glycerol are separated, after which the biodiesel is washed with distilled water at 50℃ and evaporated at 90-100℃. The density test results for the catalyst concentration of methanol at 1:2 and 0.5% NaOH showed values of 858.5 kg/m³ for reaction times of 60, 70, and 80 minutes, 858.7 kg/m³ for 90 minutes, and 858.4 kg/m³ for 100 minutes. The iodine number test results showed values of 87.2 for 60 minutes, 88.3 for 70 minutes, 90.2 for 80 minutes, 92.3 for 90 minutes, and 82.3 for 100 minutes. The research findings indicate that the obtained density and iodine number meet biodiesel quality standards and are suitable for use according to ESDM regulations.